2023
DOI: 10.1021/jacs.3c01456
|View full text |Cite
|
Sign up to set email alerts
|

Engineering C–C Bond Cleavage Activity into a P450 Monooxygenase Enzyme

Abstract: The cytochrome P450 (CYP) superfamily of heme monooxygenases has demonstrated ability to facilitate hydroxylation, desaturation, sulfoxidation, epoxidation, heteroatom dealkylation, and carbon−carbon bond formation and cleavage (lyase) reactions. Seeking to study the carbon− carbon cleavage reaction of α-hydroxy ketones in mechanistic detail using a microbial P450, we synthesized α-hydroxy ketone probes based on the physiological substrate for a well-characterized benzoic acid metabolizing P450, CYP199A4. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…VD-BM3, featuring an engineered substrate access channel, has demonstrated a high efficiency in the hydroxylation conversion rate of PG but with poor regioselectivity. An effective strategy to enhance regioselectivity is to rationally engineer residues near the substrate to bring the catalytic group of the substrate closer to the enzyme’s active site. ,, The docking results of PG and VD-BM3 complexes revealed that S72 and L437 were located within a 4-Å range of the AB ring of PG and hence were selected for saturation mutagenesis to recalibrate the distances of the D ring of PG toward the heme center (Figure A, B). S72Q -VD-BM3 was capable of producing 97% a at an 80% conversion rate (Table ), while S72H-VD-BM3 produced 97% d at a 30% conversion rate.…”
Section: Resultsmentioning
confidence: 99%
“…VD-BM3, featuring an engineered substrate access channel, has demonstrated a high efficiency in the hydroxylation conversion rate of PG but with poor regioselectivity. An effective strategy to enhance regioselectivity is to rationally engineer residues near the substrate to bring the catalytic group of the substrate closer to the enzyme’s active site. ,, The docking results of PG and VD-BM3 complexes revealed that S72 and L437 were located within a 4-Å range of the AB ring of PG and hence were selected for saturation mutagenesis to recalibrate the distances of the D ring of PG toward the heme center (Figure A, B). S72Q -VD-BM3 was capable of producing 97% a at an 80% conversion rate (Table ), while S72H-VD-BM3 produced 97% d at a 30% conversion rate.…”
Section: Resultsmentioning
confidence: 99%
“…Both substrates bound with significantly lower affinity than 4- n -propylbenzoic acid ( ≥ 95% high-spin, 0.54 μM) but with a higher affinity than 4-acetylbenzoic acid (140 μM, Table ). , …”
Section: Resultsmentioning
confidence: 99%
“…This also has an absorbance maximum at 379 nm but this was not used to determine the binding affinity (Figure ). f Despite the red shift in the Soret band, a type I difference spectrum was observed …”
Section: Resultsmentioning
confidence: 99%
“…They usually mediate a typical monooxygenation reaction via the canonical “oxygen rebound” mechanism to insert a single oxygen atom into the C–H, CC, N–H, or S–H bonds . With an increasing number of characterized P450s, the substrate radical generated by the high active oxoiron­(IV) species can initiate more complex oxidation such as C–C bond formation and cleavage. , Notably, the nucleophilic attack of the heme-Fe III hydroperoxide complex contributes to the realization of some uncommon reactions, such as epoxidation catalyzed by Fma-P450 , and C–C bond cleavage mediated by Baeyer–Villiger rearrangement catalyzed by CYP 17, JCM 1, and SdnB . Accordingly, we propose that the CtdY catalysis may proceed through a mechanism in which the carbonyl of the amide bond in 20 might be attacked by heme-Fe III hydroperoxide species resulting in the cleavage of the C–N bond.…”
Section: Resultsmentioning
confidence: 99%